2014
DOI: 10.3390/v6083019
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus Glycoprotein Incorporation, Assembly and Budding: A Three Way Dance for Infectious Particle Production

Abstract: Paramyxoviruses are a family of negative sense RNA viruses whose members cause serious diseases in humans, such as measles virus, mumps virus and respiratory syncytial virus; and in animals, such as Newcastle disease virus and rinderpest virus. Paramyxovirus particles form by assembly of the viral matrix protein, the ribonucleoprotein complex and the surface glycoproteins at the plasma membrane of infected cells and subsequent viral budding. Two major glycoproteins expressed on the viral envelope, the attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 251 publications
(348 reference statements)
0
96
0
Order By: Relevance
“…In the case of RSV, budding is unaffected by the inhibition of Vps4, suggesting that RSV uses a novel mechanism for this final step of replication. Some evidence suggests that surface glycoproteins, both F and G, could actively contribute to the budding process leading to RSV egress from infected cells (38). Although we did not detect significant changes in the levels of expression of most viral proteins, we have not investigated whether H 2 S treatment could affect their routing to the cell membrane.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the case of RSV, budding is unaffected by the inhibition of Vps4, suggesting that RSV uses a novel mechanism for this final step of replication. Some evidence suggests that surface glycoproteins, both F and G, could actively contribute to the budding process leading to RSV egress from infected cells (38). Although we did not detect significant changes in the levels of expression of most viral proteins, we have not investigated whether H 2 S treatment could affect their routing to the cell membrane.…”
Section: Discussionmentioning
confidence: 65%
“…To date, it is not known whether H 2 S, or any other endogenous gaseous transmitters, modulates ARE functions. The final step in viral assembly and budding involves a membrane scission event to separate the assembled viral particle from the host cell membrane, which often involves multivesicular body formation and the endosomal sorting complex required for transport (ESCRT) protein system, with membrane scission being performed by the ATPase Vps4 (38). In the case of RSV, budding is unaffected by the inhibition of Vps4, suggesting that RSV uses a novel mechanism for this final step of replication.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low infectivity-to-particle ratio indicates that these M protein-independent budding activities only accidentally generate infectious RNP-containing particles while mostly yielding noninfectious virus-like particles also found in F/G expression systems. Furthermore, it is likely that the envelope of the few RNP-containing particles produced in the absence of the M protein has a suboptimal composition of surface glycoproteins, which may impair the virus entry and uncoating processes (11,21). Whether the role of the M protein in the assembly process is mainly to concentrate viral components at specific sites at the plasma membrane or to ensure a defined stoichiometry of RNPs, G and F proteins require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The viral matrix (M) protein associates with the inner leaflet of the plasma membrane mediating the contact between the ribonucleoprotein (RNP) complex and the surface glycoproteins. Though the detailed role varies between different viruses, paramyxoviral M proteins are generally considered the main drivers of assembly (11). Supporting the idea of a critical role in virus particle formation and budding, NiV M protein forms virus-like particles (VLPs) when expressed on its own (12,13), and it drives apical assembly and budding of NiV virions in polarized epithelial cells (14).…”
mentioning
confidence: 99%
“…Although it has been reported that paramyxoviral and pneumoviral M proteins, by interacting with multiple cellular and viral components, play a key regulatory role in viral replication, assembly, egress, and membrane fusion (16,46,66), very little is known about the inherent ability of M to drive these discrete functions. In this study, we initiated a comprehensive structure-guided analysis to gain mechanistic insights into various M functionalities.…”
Section: Discussionmentioning
confidence: 99%